Improving The Quality of Education in Indonesia: Challenges and Opportunities - Ramadhani, Nurfadhilah (International Journal of Education and Learning Studies, 2025)
Education is a crucial aspect of a nation's development. As a developing country, Indonesia faces significant challenges in improving the quality of education. These challenges include a lack of adequate educational infrastructure, a shortage of qualified teachers, and a lack of equitable access to education. However, there are also significant opportunities to improve the quality of education in Indonesia, such as technological advances that can be leveraged to improve access and quality. This article will discuss the challenges and opportunities in improving the quality of education in Indonesia, as well as strategies that can be implemented to improve the quality of education. Therefore, it is hoped that this article will contribute to efforts to improve the quality of education in Indonesia.